Immunomodulatory Medication Use in Newly Diagnosed Youth With Systemic Lupus Erythematosus. Issue 11 (13th September 2021) - Davis, Alaina; Chang, Joyce; Shapiro, Sarah; Klein‐Gitelman, Marisa; Faerber, Jennifer; Katcoff, Hannah; Cidav, Zuleyha; Mandell, David S.; Knight, Andrea
Abstract : Objective: To examine glucocorticoid‐sparing immunomodulatory medication use in youth with systemic lupus erythematosus (SLE) during their first year of care. Methods: We conducted a retrospective cohort study using administrative claims for 2000 to 2013 from Clinformatics DataMart for youth ages 10–24 years with an incident diagnosis of SLE (≥3 International Classification of Diseases, Ninth Revision codes for SLE [710.0], each >30 days apart). We determined the proportion of subjects filling a prescription for immunomodulatory medications within 12 months of the first SLE code (index date). We used multivariable regression to examine associations between demographic/disease factors and time to prescription fill in the first year, and also between prescription fill at any time after the index date. Results: We identified 532 youth with an incident SLE diagnosis, of which 413 (78%) had a glucocorticoid‐sparing immunomodulatory prescription fill in the first year. Prescriptions for hydroxychloroquine and immunosuppressants were filled in the first year by 366 youth (69%) and by 182 (34%), respectively. Those with adult‐onset (versus childhood‐onset) disease were less likely to fill an immunomodulatory medication by 12 months. No other statistically significant associations were found, although there was increasing likelihood of immunomodulatory medication fills with each subsequent calendar year. Conclusion: Among youth with newly diagnosed SLE, hydroxychloroquine use is prevalent although not universal, and prescription immunosuppressant use is notably low during the first year of care. Further research is needed to identify factors contributing to suboptimal immunomodulatory medication use during the first year of care.